Rainwater Tank Systems for Urban Water Supply Design, Yield, Energy, Health Risks, Economics and Social Perceptions - Sharma, Ashok; Begbie, Donald (IWA Publishing, 2015)
Rainwater tank systems have been widely adopted across the world to provide a safe local source of water in underdeveloped rural areas, and as a substitution for mains water for non potable end uses in water stressed urban areas. They also provide flood control in monsoonal climates like Korea or in combined sewer systems like in Germany. The importance of these systems in cities has grown, as water managers seek to provide a range of decentralised solutions to supply constraints of current water supply systems, whilst reducing the impact of urban development on the natural environment, and increasing resilience to climate change. Rainwater Tank Systems for Urban Water Supply is based on a comprehensive, multi-million dollar research program that was undertaken in South East Queensland (SEQ) Australia in response to the Millennium drought when the water supply level in the regions drinking water dams dropped to 17% in July 2007 and the area came close to running out of water.